(3QSGdI GdCfhGQ GdbOSjI aj HjGf BOGH GdYHhOjIs - (3YHO GdhgGH Hf CMeO Hf Ydj GdnMnfaj, fSHg Edi eMeO GHf GdMfajI, GdTYQGfj, CHh eMeO , J (B973 (3g`s ((3CMeO Hf CMeO GdRhGhi s)
(3ChdgG (B:s
(3Chd GdehLhO efg bhdg (B: (3de jRd eahVkG Edjg bHd GdYHO heYg hHYOg aJahjV GdYHO TghOge Cf GdGeQ de jRd eahVkG Edjg s
(3BNQgG (B:s
(3hfSCd Gddg JYGdi Cf jMbbfG HGdYHhOjI dg Efg Ydi cd TF bOjQ hYVhg hGSY hGdMeO ddg hMOg JeJ GdQSGdI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B180s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B194s
Keywords: (3GdJUha hGdBOGH GdTQYjIs